2020
DOI: 10.1186/s13673-020-00228-8
|View full text |Cite
|
Sign up to set email alerts
|

CNN-based 3D object classification using Hough space of LiDAR point clouds

Abstract: With the wide application of Light Detection and Ranging (LiDAR) in the collection of high-precision environmental point cloud information, three-dimensional (3D) object classification from point clouds has become an important research topic. However, the characteristics of LiDAR point clouds, such as unstructured distribution, disordered arrangement, and large amounts of data, typically result in high computational complexity and make it very difficult to classify 3D objects. Thus, this paper proposes a Convo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…It achieved a substantial improvement over ZFNet, which was the winner in 2013 [65]. In another study, Wei et al proposed a CNN based 3D object classification model and achieved an accuracy of up to 93.3% [66]. The network architecture of GoogLeNet differs from other models because a convolution layer of 1 × 1 kernels with ReLU activation is used in the middle of the model.…”
Section: Googlenet (Inception Model)mentioning
confidence: 99%
“…It achieved a substantial improvement over ZFNet, which was the winner in 2013 [65]. In another study, Wei et al proposed a CNN based 3D object classification model and achieved an accuracy of up to 93.3% [66]. The network architecture of GoogLeNet differs from other models because a convolution layer of 1 × 1 kernels with ReLU activation is used in the middle of the model.…”
Section: Googlenet (Inception Model)mentioning
confidence: 99%
“…The method developed by Cui et al [20] was used for vehicle classification before detecting the queue length. Song et al [23] developed a CNN-based 3D object classification using Hough space of LiDAR point clouds. Premebida et al [24] developed a Gaussian Mixture Model classifier to distinguish vehicles and pedestrians from the LiDAR data.…”
Section: Related Workmentioning
confidence: 99%
“…PointNet++ (Qi et al, 2017b) can process more fine-grained patterns and complex scenes. (Song et al, 2020) explains how points of segmented objects can be identified using CNN's and Hough transformations. Hough transformations are a commonly used used feature extraction method in the 2D computer vision domain (Cantoni and Mattia, 2013).…”
Section: Related Workmentioning
confidence: 99%